Increasing detection of asymptomatic syphilis in HIV patients. Issue 3 (27th May 2005) - Cohen, C E; Winston, A; Asboe, D; Boag, F; Mandalia, S; Azadian, B; Hawkins, D A
Abstract : Background/objectives: The burden of new syphilis diagnoses in London has mainly been in men who have sex with men (MSM), many of whom are co-infected with HIV. Our HIV unit introduced regular serological screening for syphilis during routine follow up care to detect patients who may be at risk of asymptomatic infection. We assessed if this remained an effective and necessary strategy in the second year since introduction. Methods: All HIV outpatients with newly positive syphilis serology between 1 May 2002 and 30 April 2003 were identified using a prospectively collected database. Only patients who were asymptomatic at the time of screening were included (cohort B). They were compared to patients in the exact preceding year (cohort A). Results: 2655 patients had at least one CD4 count measured in the period (surrogate marker for patients having routine follow up bloods), of whom 2389 (90%) had syphilis serology performed. 40 individuals were found to have early asymptomatic infection (two were re-infections), compared to 26 patients in cohort A. These 40 patients represented 36% of all patients with infectious syphilis treated within our department and 56% of those who were HIV positive. The event rate in cohort B was 7.3 per 1000 patient years (CI 5.2 to 9.9) compared to 2.8 (CI 1.8 to 4.0) in cohort A. Conclusion: Routine screening is effective and has detected increasing numbers of HIV outpatients with early asymptomatic syphilis. Our department will continue this strategy for all HIV patients during their follow up care. We recommend that other units adopt similar initiatives that assist with regional control of the UK syphilis epidemic.